Hubungan Antara Literasi TIK dan Motivasi terhadap Hasil Belajar Siswa SMK - Agung Winarno; Vianita Diani Ashari (SAP (Susunan Artikel Pendidikan), 2022)
Learning outcomes are influenced by many aspects, both internal and external to the students. This reasearch is to find out the relationship between ICT literacy and motivation on student learning outcomes. The approach used explanatory quantitative, the sample used was 38 students. Data collection was conducted using questionnaires and interviews, as well as documentation related to learning outcomes. Data analysis used descriptive statistics and inferential multiple linear regression and hypothesis testing. The results showed that the ICT literacy and student motivation levels were in a good category. ICT literacy had a positive effect on student learning outcomes, motivation had no significant effect on learning outcomes, and simultaneously both variable influences student learning outcomes.